Skills identification of the extent of dietetics through the experiences of internships - Lucas, C. (2008)
In this Case Study, we want recognize the aquisition of Skills ("Benchmark") of Dietitian, through Interships. Method: Comparison between three conceptual points: Objectives of the pratice placement learning, their Scale of acessessment and skills that "Benchmark" defends. It has been conrrespondence between 28 itens relating to the parameters recomended basic academics and professionals in "Benchmark", and,24 itens contituents of the Scale of Evaluation of the "Pratice Placement Learning Pedagogic Guide", to the studants of Dietetics. From the scale of acessment, 85% of students approved, are the aquisition of skills of "Benchmark".